Analisis Kemampuan Menulis Permulaan Kelas 1 SD di Komplek Unand Blok D - Nur Azizah; Salsabila Idha Putri Sasa; Chandra Chandra; Ari Suriani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research on the analysis of beginning writing skills is motivated by students' understanding of writing and completing letters, words and simple sentences. With the aim that students understand how to write productively and descriptively and are able to convey their ideas and ideas through writing. Data collection in this study used a qualitative approach with the type of case study research (case study) and then oriented through observation, giving practice questions and documentation. After collecting data, there are several core competencies that become the findings of researchers, namely: a) students are able to write their own loose letter symbols and conjoined letters, b) students are able to complete the overlapping words, 3) students are able to write simple sentences through pictures.